Can a Naturalistic Explanation of Miracles Be Satisfactory? The Case of the Man Born Blind (John 9:1-12) - Rucki, Mirosław (Studia Philosophiae Christianae, 2025)
Naturalism rejects the possibility of something being explained independently of the material reality given in empirical cognition. In particular, miracles have to be explained in a naturalistic way to keep this rejection valid. Nevertheless, it is an empirical question itself what exactly defines a miracle. The English word “miracle” means “an extraordinary and welcome event that manifests or is attributed to divine intervention in human affairs” (The New Penguin English Dictionary). In fact, the Biblical account introduces the term “miracle” in the context of the empirical experience of an entire nation. The Hebrew words ומפתים אותת (‘signs and miracles’) are used, as follows: “And the Lord shewed signs and wonders, great and sore, upon Egypt, upon Pharaoh, and upon all his household, before our eyes” (Deut 6:22, KJV). Notably, these wonders had been announced and performed in the context of the survival and death threat of a nation. It was not just an exciting show religiously explained, it was a disaster escaped via the strict following of the instructions, which enabled us to explain the meaning of these ‘signs’. Since the meaning of the message was the main component of the miracles, no naturalistic explanation of the events could be satisfactory. Methodological naturalism can be applied to natural laws, but not to interpersonal communication or message interpretation. In this context, the healing of the man born blind (John 9:1-12) appears as another public experience with a verifiable initial state, a performed action and a final result. While the established facts passed verification successfully, it was nonetheless necessary to reject the facts in order to reject the message behind them. ---------------------------------------- Zgłoszono: 23/07/2025. Zrecenzowano: 22/09/2025. Zaakceptowano do publikacji: 17/10/2025.